Study of Cultural Values of Panah Dance in the Ohoi Ngefuit Community Using Song Instruments in Southeast Maluku Regency - Roy Marthen Rahanra (Britain International for Academic Research (BIAR-Publisher), 2022)
The history of civilization of the Ohoi Ngefuit people proves that the majority of the Ohoi Ngefuit people are the result of the migration of the Balinese people in ancient times, this can be seen from the cultural similarities and the performances of traditional rituals that are similar to the traditional Balinese culture and rituals. This Panah Dance originally came from a war dance, using bows and arrows as properties that can inspire and inflame the courage of men, but it is different from the Panah Dance in the ohoi ngefuit Panah Dance which is used by using ynayian instruments by the dancers. The Panah Dance of the ohoi ngefut community is different from the Kei people in the Kei islands. This research uses a descriptive method. The purpose of this study is to find out how much the Panah Dance culture of the Ohoi Ngefuit community is maintained until now.